PENGARUH INOVASI PRODUK, KUALITAS PRODUK DAN DESAIN KEMASAN TERHADAP KEPUTUSAN PEMBELIAN PRODUK KOSMETIK WARDAH: PENGARUH INOVASI PRODUK, KUALITAS PRODUK, DAN DESAIN KEMASAN TERHADAP KEPUTUSAN PEMBELIAN PRODUK KOSMETIK WARDAH - Natasha Maharani; Rahmawati Azizah -; Arseta Yudha Lesmana; Ria Octavia (Jurnal Inovasi, Keuangan, Manajemen dan Akuntansi, 2025)
This study aims to examine the effect of product innovation, product quality, and packaging design on the purchase decision of Wardah cosmetic products in Bandar Lampung. The type of research used is quantitative research. The data utilized are primary data, obtained from the results of a questionnaire. Data collection was conducted by distributing the questionnaire to 150 individuals. The respondent criteria included consumers who had purchased and used Wardah cosmetics within the last 6 months and were at least 17 years old. The data collection method employed non probability sampling, with the purposive sampling technique used to select participants. Data were processed and analyzed using SmartPLS version 3 and SPSS version 23 to examine respondent characteristics. The results of this study indicate that product quality and packaging design have a significant effect on purchase decisions, while product innovation does not affect purchase decisions. The limitations of this study include only distributing the questionnaire in Bandar Lampung and that the results show that product innovation does not influence purchase decisions, indicating that there is no interrelationship between the variables studied.